Ferroptosis-Related Gene MT1G as a Novel Biomarker Correlated With Prognosis and Immune Infiltration in Colorectal Cancer - Peng, Bi; Peng, Jinwu; Kang, Fanhua; Zhang, Wenqin; Peng, Emin; He, Qingchun (Frontiers in Cell and Developmental Biology, 2022)
Ferroptosis, a newly discovered way of cell death, has been proved to be involved in the oncogenesis and development of cancers, including colorectal cancer (CRC). Here, through identifying the differentially expressed genes (DEGs) from three CRC transcriptome microarray datasets (GSE20842, GSE23878 and GSE25070), we found that the expression of MT1G was significantly decreased in CRC tissues. And the patients with high level of MT1G displayed a poor prognosis. Quantitative PCR (qPCR) further confirmed the down-regulated MT1G in two CRC cells, HCT8 and HCT116. Colony Forming Assay indicated that MT1G overexpression exhibited a remarkable inhibition of cell proliferation in HCT8 and HCT116 cells. Additionally, we explored the co-expression genes of MT1G to gain a better understanding of its potential signaling pathways. Aberrantly expressed MT1G also affected the immune response of CRC patients. Collectively, these findings might deepen our comprehension on the potential biological implications of MT1G in CRC.